2018
DOI: 10.1016/j.scr.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose to cryopreserve human pluripotent stem cells

Abstract: The successful exploitation of human pluripotent stem cells (hPSCs) for research, translational or commercial reasons requires the implementation of a simple and efficient cryopreservation method. Cryopreservation is usually performed with dimethylsulphoxide (DMSO), in addition to animal proteins. However, even at sub-toxic levels, DMSO diminishes the pluripotency capacity of hPSCs and affects their epigenetic system by acting on the three DNA methyltransferases (Dnmts) and histone modification enzymes. Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Moreover, Ntai et al also reported that the time of preservation was no obvious influence on preservation. Using different CPAs to preserve pluripotent stem cells, the authors found that the viability did not differ between cells preserved for 7 days and those preserved for 30 days [ 39 ]. Therefore, we evaluated the outcome at 30 days of preservation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ntai et al also reported that the time of preservation was no obvious influence on preservation. Using different CPAs to preserve pluripotent stem cells, the authors found that the viability did not differ between cells preserved for 7 days and those preserved for 30 days [ 39 ]. Therefore, we evaluated the outcome at 30 days of preservation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we observed an improvement in the quality of the recovered cells over time. Many researchers have reported the substitution or combination of DMSO with other cryoprotectants, such as ethylene glycol or polyethylene glycol [ 55 , 63 , 68 , 69 , 70 , 71 ]. However, these cryoprotectants were shown to be more genotoxic than DMSO when cryopreserving human oocytes [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to multiple cryoprotective properties, selected disaccharides, such as sucrose and trehalose, are widely used in cryopreservation practice as additives to various freezing [2,51] and vitrification solutions [15,33,83]. Conceptually, combined introduction of sugars into cryopreservation media and their pre-freeze loading into cells serves as an alternative to conventional cryopreservation workflow.…”
Section: Discussionmentioning
confidence: 99%